2017
DOI: 10.1590/1806-93042017000300003
|View full text |Cite
|
Sign up to set email alerts
|

Access to child care services in the Northeast and in the South Regions of Brazil

Abstract: Objectives: to estimate the incomplete follow-up on child care services and the associated factors in the municipalities in the Northeast (PR= 0.72;) and 100 to 999 thousand inhabitants in the South (PR=0.69;; the South has the greatest income quartile (RP=0.77; and has six or more prenatal consultations (PR=0.83;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
2
0
3
Order By: Relevance
“…Com relação ao seguimento na puericultura, alguns estudos mostraram que mais de 90% das crianças nordestinas investigadas frequentaram a puericultura e cerca de dois terços delas tiveram pelo menos 7 acompanhamentos 17,18 . A prevalência de crianças nordestinas com puericultura incompleta foi de 53,6% 19 . Quando comparado a outras regiões brasileiras, o Nordeste exibe fatores que podem estar associados à dificuldade de acompanhamento, como grande território geográfico, tamanho populacional e status econômico da região.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Com relação ao seguimento na puericultura, alguns estudos mostraram que mais de 90% das crianças nordestinas investigadas frequentaram a puericultura e cerca de dois terços delas tiveram pelo menos 7 acompanhamentos 17,18 . A prevalência de crianças nordestinas com puericultura incompleta foi de 53,6% 19 . Quando comparado a outras regiões brasileiras, o Nordeste exibe fatores que podem estar associados à dificuldade de acompanhamento, como grande território geográfico, tamanho populacional e status econômico da região.…”
Section: Discussionunclassified
“…Quando comparado a outras regiões brasileiras, o Nordeste exibe fatores que podem estar associados à dificuldade de acompanhamento, como grande território geográfico, tamanho populacional e status econômico da região. Portanto, estas crianças estão mais propensas a não terem acompanhamento de saúde completo 19 .…”
Section: Discussionunclassified
“…São de grande importância na consulta de no acesso aos serviços de saúde. As características econômicas, de escolaridade e de utilização do serviço de saúde exerceram as maiores influências nos resultados para as duas regiões (21) . Dentre as dificuldades identificadas, no geral, o horário das consultas foi um dos fatores que dificultavam o acesso de mães com os filhos à puericultura.…”
Section: Discussionunclassified
“…In the study conducted by Vitolo, Gama and Campagnolo (2010), the authors suggest that the factors associated with the lack of regular use of the childcare service were maternal schooling ≤ 8, non-nuclear family structure and not being an only child, in addition to the belief that monitoring in the childcare service is unnecessary if there is no child's illness. In a comparative study between the South and Northeast regions, Santos et al (2017) found factors associated with the mother's participation in child care: the economic characteristics, education and use of the health service had the greatest influence on the results of follow-up for child care for both regions.…”
Section: Mothers Of Children Under Two Years Of Agementioning
confidence: 99%